Application of a core genome sequence typing (cgMLST) pipeline for surveillance of Clostridioides difficile in China - Wang, Yuan Yuan; Xie, Lu; Zhang, Wen Zhu; Du, Xiao li; Li, Wen Ge; Bia, Lu Lu; Cui, Zhi Gang; Wu, Yuan; Lu, Jin Xing (Frontiers in Cellular and Infection Microbiology, 2023)
Clostridioides difficile (C. difficile) is a nosocomial bacterial pathogen that causes antibiotic-associated diarrhea mediated by cellular exotoxins secreted into the intestine during bacterial growth. Multilocus sequence typing (MLST) and PCR ribotyping are the main molecular typing for C. difficile. whole genome sequencing (WGS) core genome multilocus sequence typing (cgMLST) was developed for genetic evolution and outbreak investigation of C. difficile with higher precision and accuracy. A total of 699 whole (complete and draft) genome sequences of distinct C. difficile strains were used in this study to identify core gene set (2469 core genes) and the cgMLST scheme for the phylogeny analysis of C. difficile. This cgMLST pipeline was then carried the Chinese Pathogen Identification Net (China PIN) for surveillance of C. difficile in China. Within the China PIN, 195 WGS of C. difficile and an outbreak of CDI with 12 WGS of C. difficile were used to evaluate the cgMLST pipeline. The result displayed that mostly tested C. difficile isolates could be successfully divided into 5 classic clades and the outbreak event was also successfully identified. The results are meaningful and offer a practicable pipeline for a national-wide surveillance of C. difficile in China.